Dose–Volume Predictors for Patient-reported Late Diarrhoea, Faecal Incontinence and Urgency after Pelvic Radiotherapy. Issue 8 (August 2021) - Jadon, R.; Hanna, L.; Parsons, P.; Staffurth, J.
Abstract: Aims: Pelvic radiotherapy adds significantly to the curative treatment of many pelvic malignancies. However, this cure comes at a cost for many patients, where late bowel toxicities, such as faecal incontinence, urgency and diarrhoea, adversely affect quality of life. Despite the implementation of advanced radiotherapy techniques in many centres, there are deficiencies in our knowledge of how to make best use of these techniques to minimise these late toxicities, with dose–volume constraints specifically for late effects needing definition. The aims of this study were to establish dose–volume predictors for patient-reported late bowel toxicities and derive constraints for clinical use to reduce the risk of these toxicities. Materials and methods: All radiotherapy patients treated in our institution between 2012 and 2014 for gynaecological and urological cancers (bladder, prostate where pelvic nodes are treated) were identified. Patients were sent patient-reported toxicity questionnaires at 12 and 24 months after treatment. Planning computed tomography scans were retrospectively contoured with different definitions of bowel as organs at risk (OARs). Dose–volume data for each OAR were collected and predictors of these toxicities found using multivariate analysis. For those dose–volume predictors found to be significant on multivariate analysis, statistically significant and clinically relevant dose–volume constraints were derived. Furthermore, data collected were used to validate constraints from published studies. Results: Faecal urgency, incontinence and diarrhoea rates were found in 52, 23.5 and 18.7% of the 203 patients included at 12 months following radiotherapy. Dose–volume parameters for sigmoid colon and large bowel were significant for these toxicities, and constraints for these OARs were derived, which are promising. A previously published constraint for bowel loops was validated with our data. Conclusions: The sigmoid colon and large bowel are important OARs for the development of faecal urgency, incontinence and diarrhoea. Promising constraints for these OARs were derived, which require further validation before prospective clinical use. Highlights: Patient-reported late bowel toxicities from pelvic radiotherapy are unfortunately common and debilitating. Detailed knowledge of dose-volume predictors and constraints to reduce these late toxicities is needed to allow us to make best use of advanced radiotherapy techniques. This study highlights dose-volume predictors for late diarrhoea, incontinence and urgency. We found dose-volume parameters to sigmoid colon and large bowel as being predictive of these toxicities, and these should be further considered as organs at risk. Published constraints for bowel loops are validated with this dataset and should be used in clinical protocols.